(untitled) (diségno, 2023)
Drawing is form, and this form is always a new creation, a new represented world, a first step toward an abstract geometry. A description of the sky dome, a view from above of a site interpreted in its broad outlines, so that geometry can speak the language of intelligible forms and their relationships. From the earliest days, ‘drawing’ creeps into the representation of the world by flanking artistic interpretation with geometry and abstraction. It is already an architectural drawing from the very beginning. [read more]